Embracing plurality through oral language - Nguyen, Bich; Oliver, Rhonda; Rochecouste, J. (Routledge Taylor Francis Group, 2015)
The transmission and dissemination of knowledge in Aboriginal societies for the most part occurs orally in an Aboriginal language or in Aboriginal English. However, whilst support is given to speaking skills in Indigenous communities, in our education system less emphasis is given to developing equivalent oral communicative competence in Standard Australian English (SAE). Instead the focus is given to the ongoing assessment of reading and writing skills and grammatical knowledge – this is in direct contrast to the existing language experience of Aboriginal students. Therefore, for Aboriginal students to participate in mainstream society, we suggest that there is a need to nurture oral language skills in SAE and provide learners with the experience to develop their code-switching ability to maintain continuity with their first language or dialect. Drawing on previous research that we and others have undertaken at several schools, this paper highlights the need for three fundamental changes to take place within language education: (1) school policies to change and explicitly accept and support Aboriginal English in code-switching situations; (2) familiarity among school staff about the major differences between Aboriginal English and SAE; and (3) tasks that focus on developing and practising the ‘when, why and how’ of code-switching.